The Kharijites’ Interpretation of Hadith and its Impact on the Islamic Nation - Harahsheh, Eid Abed Alhaleem Maslat (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: The study aims to shed light on the Kharijites’ falsified interpretations of hadith and to respond to them. Moreover, it aims to show the impact of these interpretations on the Islamic nation. Methods: The inductive approach is adopted throughout the study to investigate the issues in question. In addition, the study uses the critical approach to highlight the position of the Kharijites on Sunnah. Results: The results reveal that as the Kharijites interpreted many hadiths, they lacked jurisprudence and did not distinguish between general and specific texts or absolute and restricted texts. The study also shows the effects of these interpretations include accusing many Muslims of disbelief (takfīr), which entails legalizing their murder and accusing sinners of apostasy. The Kharijites’ interpretation of hadith also had many negative effects on the Islamic nation as it led to the lack of unity among Muslims and the distortion of the image of Islam. Conclusion: The study calls for challenging the falsified interpretations of religious texts because of their destructive effect on the Islamic nation. It also recommends clarifying some Islamic concepts and clearing up common misunderstandings and misconceptions about Islam which distorted its image, as they are exploited by the enemies of Islam for malicious purposes.